Representasi Pendidikan Moral dan Sosial dalam Lirik Lagu Religi (Kajian Semiotika pada Lagu "Cerminan Jiwa" Karya Wafiq Azizah) - Hosniyeh Hosniyeh (Jurnal Tinta, 2026)
This study aims to analyze the denotative, connotative, and mythical meanings in the lyrics of Wafiq Azizah's song Cerminan Jiwa using Roland Barthes' semiotic approach. The research method used is descriptive qualitative, with data collection techniques consisting of observing and taking notes on the song's lyrics. The data were analyzed qualitatively through three stages: data reduction, data presentation, and conclusion drawing. The results show that at the denotative level, the song's lyrics convey literal messages about feelings, emotional differences, steadfastness, and recommendations for maintaining a healthy attitude in everyday life. At the connotative level, the lyrics represent the complexity of human emotional experiences, such as inner struggle, vulnerability, steadfastness, and moral values such as humility, honesty, and self-acceptance. Meanwhile, at the mythical level, the song Cerminan Jiwa builds a worldview rooted in religious and cultural values, such as belief in destiny, awareness of the transience of the world, and simplicity as an ideal value in social life. Thus, this song functions not only as a musical work of art but also as a medium for reflecting on human values and social ideologies relevant to society.